The Effect of Population Growth and Economic Growth on The Level of Poor Population in North Tapanuli Regency 2013 – 2024 - Dewi Sartika Simanjuntak; Annisa Ilmi Faried; Uswatun Hasanah (International Journal of Economics and Management, 2026)
This study aims to analyze the effect of population growth and economic growth on the poverty rate in North Tapanuli Regency for the period 2013–2024. The quantitative approach uses secondary time series data from the Central Statistics Agency (BPS). The analysis was conducted through multiple linear regression using the Ordinary Least Squares (OLS) method by including the dummy variable D2020 to accommodate the structural break of the COVID-19 pandemic. Stationarity tests used Augmented Dickey-Fuller (ADF), classical assumption tests (Jarque-Bera normality, VIF multicollinearity, White heteroscedasticity, Breusch-Godfrey autocorrelation), and the Cochrane-Orcutt AR(1) correction. The results show that population growth (H1) and economic growth (H2) have no significant effect partially (p > 0.05). However, simultaneously both have a significant effect on the poverty rate (F = 5.14; p = 0.029; R² = 65.85%). Structural break 2020 was the most dominant variable (β = -2.133; p < 0.05). This finding indicates that regional economic growth is not yet fully inclusive. Policy implications are directed at strengthening the agricultural sector, developing MSMEs, expanding vocational training, and equitable distribution of social protection.